2021
DOI: 10.3390/ijerph18189741
|View full text |Cite
|
Sign up to set email alerts
|

The Dental Aesthetic Index and Its Association with Dental Caries, Dental Plaque and Socio-Demographic Variables in Schoolchildren Aged 12 and 15 Years

Abstract: The Dental Aesthetic Index (DAI) was determined in 12- and 15-year-old schoolchildren to ascertain the prevalence of malocclusion and to assess its association with dental caries experience, dental plaque accumulation, and socio-demographic variables. We performed a cross-sectional study with a stratified two-stage sampling design. An oral health survey and oral examination were conducted, and socio-demographic data were recorded. The sample comprised 1453 schoolchildren aged 12 (868) and 15 (585). These two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…However, there were some studies which have findings not similar to our study. These studies showed that DAI require less time in assessment of need for orthodontic treatment by assessment of dental aesthetics [ 2 - 6 ]. Since its introduction in 1986, the Dental Aesthetic Index (DAI) has been extensively used in numerous epidemiological studies to evaluate the prevalence of malocclusion and the need for orthodontic care [ 13 - 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there were some studies which have findings not similar to our study. These studies showed that DAI require less time in assessment of need for orthodontic treatment by assessment of dental aesthetics [ 2 - 6 ]. Since its introduction in 1986, the Dental Aesthetic Index (DAI) has been extensively used in numerous epidemiological studies to evaluate the prevalence of malocclusion and the need for orthodontic care [ 13 - 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the last three decades, there has been a significant surge of requests for orthodontic therapy [ 1 , 2 ]. The social science studies show that an unsatisfactory dental appearance can stigmatize, obstruct professional development and community acceptance, promote discrimination, and negatively impact self-concept provide the basis for recommendations for treatment based on aesthetic impairment [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saliva-based caries risk assessment has gained attention as a non-invasive and convenient method for evaluating the patients' oral condition; many dental clinics perform caries risk assessments using saliva. However, reports addressing the impact of maxillofacial morphology on salivary characteristics are scarce, although malocclusion has been reported to increase the risk of caries [24,25]. Furthermore, the correlation between maxillofacial morphology and caries risk remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The DAI is distinguished by the fact that it produces a single score for a given patient, incorporating the subject's appearance and function. The Index has been used in numerous epidemiological analyses on large sets of patients to determine the need for orthodontic treatment in a selected age group [1,2,3], ethnic group [4], country [5] or region [6,7]. According to Chrystiane F. Cardoso et al DAI is a reliable tool for conducting epidemiological studies [8].…”
Section: Introductionmentioning
confidence: 99%